Art and Rebirth: the Theme of Humanistic Criticism - SHI, Chenggang (Journal of Research for Christianity in China (JRCC), 2023)
Humanistic criticism, as a special case in the contemporary art criticism theory, emphasizes the transcendent humanistic spirit and uses the Christian thought. This paper reviews the creative process and text clues of the theory, summarizes its theme as "art and rebirth", and explains the connotation according to the Christian thought: The "reality" of art comes from the integration with the "ultimate reality", which is expressed as the reflection on the "existence pattern"; the content of spiritual art is mostly "Immanuel" concept, which can convey sacred news and show the secular content; "rebirth" represents "the real renewal of life". The article points out that humanistic criticism not only cleans out people's living area and the root cause of existence through artistic criticism, but also carries out modern criticism with Chinese characteristics based on Christian culture. It shows the ideological value in both the innovation of art criticism and the exploration of Christian thought.
Keywords: Humanistic criticism, Christian thought, Art and rebirth